Cost-effectiveness Analysis on Magnetic Harvesting of Algal Cells. (2017) - Xu, Yunfeng; Fu, Yu; Zhang, Dayi
Abstract: This study investigated the magnetic harvesting of algae via magnetic nanoparticles (MNPs). MNPs achieved high harvesting efficiency, over 95.0%, for various algal strains and could be effectively reactivated for low-cost algae separation. Comparing different harvesting efficiency, synthesis cost and reactivation methods, the present work evaluated the cost-effectiveness of different MNPs types and discussed the key factors affecting harvesting cost. Our results indicated a significant low cost and high harvesting effectiveness by naked MNPs and ultrasonic reactivation, though surface modified MNPs had higher harvesting capacity. Given the fact that algae harvesting is one of the most cost-consumption step in bioenergy production, we suggested magnetic algae harvesting with naked and reactivated MNPs as the most cost-effective technique for future industrial application.